Comparing Enterovirus 71 with Coxsackievirus A16 by analyzing nucleotide sequences and antigenicity of recombinant proteins of VP1s and VP4s - Li, Yuyun (BioMed Central, 2011)
BACKGROUND: Enterovirus 71 (EV71) and Coxsackievirus A16 (CA16) are two major etiological agents of Hand, Foot and Mouth Disease (HFMD). EV71 is associated with severe cases but not CA16. The mechanisms contributed to the different pathogenesis of these two viruses are unknown. VP1 and VP4 are two major structural proteins of these viruses, and should be paid close attention to. RESULTS: The sequences of vp1s from 14 EV71 and 14 CA16, and vp4s from 10 EV71 and 1 CA16 isolated in this study during 2007 to 2009 HFMD seasons were analyzed together with the corresponding sequences available in GenBank using DNAStar and MEGA 4.0. Phylogenetic analysis of complete vp1s or vp4s showed that EV71 isolated in Beijing belonged to C4 and CA16 belonged to lineage B2 (lineage C). VP1s and VP4s from 4 strains of viruses expressed in E. coli BL21 cells were used to detect IgM and IgG in human sera by Western Blot. The detection of IgM against VP1s of EV71 and CA16 showed consistent results with current infection, while none of the sera were positive against VP4s of EV71 and CA16. There was significant difference in the positive rates between EV71 VP1 and CA16 VP1 (χ(2 )= 5.02, P < 0.05) as well as EV71 VP4 and CA16 VP4 (χ(2 )= 15.30, P < 0.01) in the detection of IgG against recombinant proteins with same batch of serum samples. The sera-positive rate of IgG against VP1 was higher than that against VP4 for both EV71 (χ(2 )= 26.47, P < 0.01) and CA16 (χ(2 )= 16.78, P < 0.01), which might be because of different positions of VP1 and VP4 in the capsid of the viruses. CONCLUSIONS: EV71 and CA16 were highly diverse in the nucleotide sequences of vp1s and vp4s. The sera positive rates of VP1 and VP4 of EV71 were lower than those of CA16 respectively, which suggested a less exposure rate to EV71 than CA16 in Beijing population. Human serum antibodies detected by Western blot using VP1s and VP4s as antigen indicated that the immunological reaction to VP1 and VP4 of both EV71 and CA16 was different.